Efek Fortifikasi Asam Folat pada Beras Premiks Lokal terhadap Konsentrasi dan Hasil Belajar pada Santri - Syam, Aminuddin; Taslim, Nurpudji Astuti; Budu, Budu; Jafar, Nurhaedar; Jufri, Muhammad (Media Kesehatan Masyarakat Indonesia, 2019)
Deficiency of iron intake and folic acid intake can cause a shortage of concentration and student achievement. The purpose of this study explains the effect of giving fortified rice with folic acid on concentration and Student learning outcome. This study is an experimental using the Double-Blind Randomized Control Trial Design. The population is students in the Annihaya boarding school is 603 people. The sample is 80 male students of aged 12-15 years. The sample was divided into four groups, namely groups given fortification rice (anemia and non-anemia) and groups given non-fortification rice (anemia and non-anemia). The results showed that the greatest decrease in concentration scores in the intervention group was -2,75, while in the control group, it decreased by -1,65 and there was no significant difference either in the group or the difference group with p value> 0,05. The increase in student learning outcomes in the intervention group was 0,11 while the control group had decreased by -0,44. The results show that there were significant differences in the intervention group before and after the intervention. But statistical tests showed there were no differences in student learning outcomes scores between the intervention group and the control group (p>0,05). The conclusion is that the concentration of students decreased in all groups after the intervention and the greatest decrease occurred in the group given non-anemic fortified rice. Student learning outcomes increased in all groups after the intervention and the largest increase occurred in the anemic group who were given fortified rice.